Factors associated with insulin‐induced weight gain in an Australian type 2 diabetes outpatient clinic. Issue 7 (July 2016) - Yadgar‐Yalda, R.; Colman, P. G.; Fourlanos, S.; Wentworth, J. M.
Abstract : Background: Insulin‐induced weight gain is a key concern for people with type 2 diabetes (T2D) and their treatment team. This study aimed to document the prevalence of insulin‐induced weight gain and its impact on cardiovascular risk factors in patients attending the Royal Melbourne Hospital diabetes clinic. Methods: Clinical and biochemical data were extracted from a prospective clinic database and from the hospital record. These variables were correlated with the percentage weight change 1 year after starting insulin and compared between groups with or without clinically significant weight gain, defined as more than 7% of the baseline bodyweight. Results: The population comprised 340 patients (184 male), representing 36% of people with T2D who commenced insulin at our clinic. Their mean ± SD age and duration of diabetes was 63 ± 11 and 13 ± 8 years respectively. The mean (95% CI) change in bodyweight at 1 year was 3.0 (2.5–3.5) kg, but this was not associated with deleterious changes in blood pressure or lipid profile. Weight gain was associated with higher insulin doses, the use of short‐acting insulin and with lower baseline bodyweight. Clinically significant weight gain occurred in 87 patients and was associated with glucose‐lowering regimens that included short‐acting insulin or a thiazolidinedione, whereas regimens that incorporated other oral agents, particularly sulfonylureas, were associated with less weight gain. Conclusion: In this Australian tertiary hospital population with T2D, insulin‐induced weight gain was common but was not associated with deleterious changes in blood pressure or lipids. Treatment regimens that avoid short‐acting insulin but include oral agents other than thiazolidinediones might prevent insulin‐induced weight gain in T2D.